Religiosity or Income? Factors Driving Customer Buying Interest in Islamic Insurance Products - Dede Nurohman (Shirkah: Journal of Economics and Business, 2022)
Despite the enormous potential represented by an 87% Muslim population and the growing welfare of the Muslim community in Indonesia, Islamic insurance has not grown rapidly during the past decades. The primary issues that hinder the growth of the Islamic insurance sector are thought to be people's level of income and religiosity. Therefore, this paper attempts to investigate the effect of religiosity and income on people's interest in buying Islamic insurance products. This study employed a quantitative approach with a questionnaire as a data mining technique. 200 residents of eight districts and cities in East Java, a province in Indonesia, participated as respondents in this study. The data analysis involved descriptive analysis, inferential analysis, classical assumption test, and hypothesis test. This study demonstrates that people's interest in buying Islamic insurance products is positively and significantly influenced by their religiosity and income, either partially or simultaneously. This result can be taken into account by the Islamic insurance sector when planning the best marketing plan, especially for the wealthy and fervently religious Muslim segment of society.